Structural, elastic and optical properties of rice husk silicate borotellurite glass system doped with micro and nanoparticles of erbium oxide - Sa'ad, Aliyu Umar (2018)
Successful extraction of high purity SiO2 (about 99%) from rice husk (waste) was achieved in this work using the cold acid leaching method. Glass series [(TeO2)0.7 (B2O3)0.3]1-x (SiO2)x were fabricated using the rice husk silicate (RHS) by meltquenching method. The aim was to extract a very high purity SiO2 from rice husk with no heat used in leaching to fabricate a system of silicate borotellurite glass system doped with erbium oxide and erbium oxide nanoparticles. The choice of rice husk as silicate source was to add to the commercialization of the rice husk waste management which stand at 30%. Also, to study the structural, elastic and optical properties of the glass systems for Erbium Doped Fiber Amplifier (EDFA) application. The use of rice husk silicate in a borotellurite glass system was expected to improve the glass quality in terms of both elastic and optical properties. The samples were subjected to X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR) and UV-Vis characterizations to study the structural nature and optical behavior of the glass system. Density, molar volume and ultrasonic velocities were measured to obtain the elastic constants for the various silicate proportions in the glass using ultrasonic data obtained from non-destructive ultrasonic probing technique. The glasses fabricated were found to be transparent at lower RHS concentrations (0.0-0.2) the glasses became more darkened and opaque from 30% to 40% RHS concentrations. 20% RHS was found to be the best SiO2 composition in terms of transparency, elastic and optical properties of the glasses for Er3+ ion doping. Using the 0.2 molar fraction of RHS (SiO2), a glass system of erbium/erbium NPs doped rice husk silicate borotellurite (Er/Er NPs-doped RHSBT) glass system was fabricated using the chemical composition {[(TeO2)0.7 (B2O3)0.3]0.8 (SiO2)0.2}1-x (Er2O3)x with x = 0.01, 0.02, 0.03, 0.04 and 0.05 mol was prepared using the meltquenching technique. The glasses were as well subjected to characterizations as XRD, FTIR, UV-Vis spectroscopy, photoluminescence spectroscopy and non-destructive ultrasonic probing to study the structural, elastic, optical and luminescence properties of the glasses. Theoretical elastic models of Makishima and Mackenzie, Rocherulle, bond compression and ring deformation models were used to study more on the elas tic properties and compare with the experimental data. Density and molar volume measurements were also carried out to further provide structural details while transmission electron microscopy was carried out on the erbium nanoparticles doped series to study the morphological features of the glasses. In all the three samples, the XRD showed no sharp peak indicating a glassy nature. The density and molar volume in the case of RHSBT glass system decreased with increase in SiO2 concentration. The ultrasonic velocities, elastic moduli, optical band gaps, Urbach energy, oxygen packing density (OPD), metallization criterion and transmission coefficient increased with RHS concentration increased. The theoretical elastic models confirmed the elastic moduli increase in the silicate borotellurite glass system with increasing SiO2 content as shown in the experimental study. Only the Makishima and Mackenzie model appeared to be good for the elastic properties of both the erbium oxide doped and erbium oxide NPs doped glass systems. Using McCumber theory analysis from the UV-Vis data, Absorption and Emission cross-section data was obtained and used to calculate the simple fiber gain of each sample in the two micro and nano erbium doped RHSBT glass systems. The gains were higher in the case of micro erbium doped system than the nano erbium doped system. With high refractive index of between 2.452 to 2.521 and wide effective band with in the S and C bands of between 76 to 106 nm, the micro erbium doped RHSBT glass system provides a good potential for application in the erbium doped fiber amplifiers (EDFA).